PARÁSITOS INTESTINALES DE PERROS CALLEJEROS: RIESGO A LA SALUD PÚBLICA EN SAN RAMÓN, COSTA RICA (Biocenosis, 2015)
In order to determine the health endoparasite of stray dogs and to assess soil contamination by these, we studied the soil and feces found in the park Alberto Manuel Brenes between March and April 2011. We confirmed the presence of four species of parasites in the stool and one type of parasites in the soil samples using two sampling techniques: Sheater and Saline – Lugol, resulting in 83,33% positive and 16,6% positive respectively. The parasites can be transmitted to humans, so it is necessary to manage health programs for prevention, control and eradication of parasitic zoonoses.
Keywords: Endoparasite; Soil; Pollution; Stray dogs; Stools; Public health